Radio-frequency thermodestruction of jugular sympathetic ganglion in order to destruct vasoconstriction at subarachnoid aneurysmatic hemorrhage - A. L. Krivoshapkin; A. R. Duishobayev; Ye. G. Melidi; O. A. Safronova (Бюллетень сибирской медицины)
The new method of cerebral vasospasm management is proposed. Selective radiofrequency thermodestruction of the cervical sympatethic ganglion at the С6 , С7 on the side of vasospasm has been performed. This study showed high efficiency for treatment of patients with cerebral vasospasm due to aneurysm rupture.